2018
DOI: 10.1016/j.bandc.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Topographical differences of frontal-midline theta activity reflect functional differences in cognitive control abilities

Abstract: Electrophysiological oscillations are assumed to be the core mechanism for large-scale network communication. The specific role of frontal-midline theta oscillations as cognitive control mechanism is under debate. According to the dual mechanisms of control framework, cognitive control processes can be divided into proactive and reactive control. The present study aimed at investigating the role of frontal-midline theta activity by assessing oscillations in two tasks varying in the type of cognitive control ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 53 publications
4
40
1
Order By: Relevance
“…Proskovec et al (2018) in a MEG study localized theta in the left dorsolateral prefrontal cortex and reported an increase, but their figure 3 shows the opposite pattern: after a short transient increase, theta decreased below baseline level and maintained in this state until probe presentation. Contrary to the results by Proskovec, theta continuously increased during delay period in two EEG studies in exactly the same paradigm (Berger et al, 2019;Eschmann et al, 2018). The spatial WM task employed by these three studies was first published in EEG study by Griesmayr et al (2014) 1 , which also reported a theta increase.…”
Section: Thetacontrasting
confidence: 93%
“…Proskovec et al (2018) in a MEG study localized theta in the left dorsolateral prefrontal cortex and reported an increase, but their figure 3 shows the opposite pattern: after a short transient increase, theta decreased below baseline level and maintained in this state until probe presentation. Contrary to the results by Proskovec, theta continuously increased during delay period in two EEG studies in exactly the same paradigm (Berger et al, 2019;Eschmann et al, 2018). The spatial WM task employed by these three studies was first published in EEG study by Griesmayr et al (2014) 1 , which also reported a theta increase.…”
Section: Thetacontrasting
confidence: 93%
“…Several works have shown that memory encoding and retrieval is supported by an increased synchronization of slow oscillatory activity (3-8 Hz), notably in the medial temporal lobe (Heusser, Poeppel, Ezzyat, & Davachi, 2016;Clouter, Shapiro, & Hanslmayr, 2017;Burke et al, 2014;. Alternatively, an increase of such activity in the frontal medial electrodes is also a strong correlate of the higher recruitment of cognitive control mechanisms (Cavanagh & Frank, 2014;Mückschel, Dippel, & Beste, 2017;Eschmann, Bader, & Mecklinger, 2018), that may also occur during the TNT procedure. The decrease we report here between 5 and 9 Hz might indeed reflect a mixed process of both higher neocortical inhibitory engagement and a decrease of memory replay.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has indicated that oscillations at theta frequencies (3-7 Hz in humans) are involved in navigation and spatial memory (Eschmann, Bader, & Mecklinger, 2018;Bohbot, Copara, Gotman, & Ekstrom, 2017;Hasselmo, Hinman, Dannenberg, & Stern, 2017;Namboodiri, Levy, Mihalas, Sims, & Hussain Shuler, 2016;Chakravarthy & Balasubramani, 2015;Hartley, Lever, Burgess, & O'Keefe, Figure 6. Distinct timefrequency markers for processing different types of shortcuts.…”
Section: Oscillatory Markers During Navigational Choicesmentioning
confidence: 99%